Association between High Values of D-dimer and Tissue-plasminogen Activator Activity and First Gastrointestinal Bleeding in Cirrhotic Patients - Violi, Francesco; Basili, Stefania; Ferro, Domenico; Quintarelli, Claudio; Alessandri, Cesare; Cordova, Corrado; CALC Group (Thrombosis and Haemostasis, 1996)
Cirrhotic patients with decompensated state and high serum levels of fibrin(ogen) degradation products are at high risk of bleeding. The aim of this study was to further analyse the relationship between hyperfibrinolysis and bleeding in cirrhosis by measuring plasma values of D-dimer and tissue plasminogen activator (t-PA) activity. One-hundred-twelve cirrhotic patients with oesophageal varices and without previous upper-gastrointestinal bleeding entered the study and were followed-up for 3 years. Patients were considered to have hyperfibrinolysis if they concomitantly had high values of D-dimer and t-PA activity. During the follow-up 34 (30%) patients bled. They had more severe liver failure (p = 0.0001) and variceal size (p = 0.0031) and higher prevalence of ascites (p = 0.0003), varices with red signs and hyperfibrinolysis (p = 0.0001) than patients who did not bleed. Multivariate analysis disclosed hyperfibrinolysis as the only marker predictive of bleeding (Hazard Ratio = 42.5, p <0.001). Our findings suggest that screening for hyperfibrinolysis may be useful to identify cirrhotic patients at risk of bleeding.